Violência: um gozo não balizado pelo simbólico. - Oliveira, Regina Maria Peregrino Pimentel de (2012)
This research has as its theme the link between the violence and the decline of the symbolic order, represented in the Lacanian psychoanalysis by the fall of the significant the Name-of-father and which represents sign of contemporary society. Although the violence is in the history mankind, we believe that its spread justifies a field of investigation. In this paper the violence will not be cataloged (domestic violence, urban violence, etc.) because we understand that by the cataloging of the phenomenon we would difficult the problem of its location, in view of it would be necessary enter in the matter of the existence of a victim, the subject who suffers the act. Thereby, we will discuss the violence as a contemporary symptom, as a signing of the current discontent, result of the prevalence of the drive satisfaction, where the value of sense of the symptom is subdued to its value of enjoyment. According to Lacanian psychoanalysis, in the contemporaneity does not exist more a limit offered by the exception, but what exists is a worldwide which register itself as a opened set, without a limit, beside the female sexuation which leads to the question of the enjoyment treatment when this escapes to the law. We believe that the psychoanalysis can contribute to turn the violence, as a symptom which formalizes the enjoyment, into an analytical symptom to provide to the subjects the possibility of invention of a sinthoma that can reshape the enjoyment and relieve the current discontent of the subjects, even considering that by the outlook of psychoanalysis only the subject can say from what does not go well with them (although it does not exist a knowledge previously constituted about this saying) and turn their symptom into an analysis symptom.